Domestic abolitionism and juvenile literature, 1830-1865 - De Rosa, Deborah C. (State University of New York Press, 2003)
"Deborah C. De Rosa examines the multifaceted nature of domestic abolitionism, a discourse that nineteenth-century women created to voice their political sentiments when cultural imperatives demanded their silence. For nineteenth-century women struggling to find an abolitionist voice while maintaining the codes of gender and respectability, writing children's literature was an acceptable strategy to counteract the opposition. By seizing the opportunity to write abolitionist juvenile literature, De Rosa argues, domestic abolitionists were able to enter the public arena while simultaneously maintaining their identities as exemplary mother-educators and preserving their claims to "femininity." Using close textual analyses of archival materials, De Rosa examines the convergence of discourses about slavery, gender, and children in juvenile literature from 1830 to 1865, filling an important gap in our understanding of women's literary productions about race and gender, as well as our understanding of nineteenth-century American literature more generally."--Jacket